Voter Participation in the Election of the Head and Deputy Regional Head of Banjarmasin City in 2020 During the Covid 19 Pandemic - Pery Pery; Samahuddin Samahuddin; Bachruddin Ali Akhmad (Daengku: Journal of Humanities and Social Sciences Innovation, 2022)
The purpose of this study is to find out and explain the causes of low voter participation in the election of the head and deputy regional head of Banjarmasin City in 2020 during the covid 19 pandemic. This study uses a qualitative approach with descriptive research type, data collection techniques using interviews and documentation, data analysis techniques data reduction, data presentation, conclusion drawing or verification, and the validity of the data source triangulation, technique mastulation and time triangulation. The results showed that the low voter participation in the election of the Head and Deputy Regional Head of Banjarmasin City in 2020 during the Covid 19 Pandemic was influenced by factors, namely the covid 19 factor, the weather/rain factor, the administrative factor, the work factor, and the habit factor. The low participation was due to not achieving the target set by the general election commission of the Republic of Indonesia, namely 77.5%, the target of the general election commission of Banjarmasin city of 75% was only achieved by 57.63% This research is expected to be a suggestion to election organizers to increase public awareness of the importance of voter participation in the 2020 Banjarmasin City Head and Deputy Regional Head Elections in the Covid 19 Pandemic Period in order to achieve the set targets.